Heroínas - da submissão à ação: uma análise junguiana de personagens em filme de animação - Bilotta, Fernanda Aprile (2010)
The aim of this dissertation is to examine the trajectory of some heroines of children s films produced by the animation studios Walt Disney Pictures and Dreamworks Pictures from 1937 to 2007. Therefore, the films Snow White and the Seven Dwarfs (Walt Disney Pictures, 1937), Cinderella (Walt Disney Pictures, 1950), Sleeping Beauty (Walt Disney Pictures, 1959), The Little Mermaid (Walt Disney Pictures, 1989), Beauty and the Beast (Walt Disney Pictures, 1991), Shrek! (DreamWorks Pictures, 2001), Shrek 2 (DreamWorks Pictures, 2004) and Shrek the Third (DreamWorks Pictures, 2007) were watched, summarized and analyzed in order to identify target behaviors and themes propagated by their protagonists. The elaboration was based on images, events and sequences which were significant in the composition of the characters and their development in the narratives. The theme seems closely related to the hero s archetype, which drives the process of development of consciousness, and is activated mainly in adolescence when girls and boys begin their passage to adulthood. The analysis is based on analytical psychology concepts and on the interpretation criteria suggested by Von Franz for fairy tales. The heroines shown on the film screen help to understand how the archetypes currently manifest themselves and also how they cooperate in facing and coping with many different situations. Thus, through imaginary and symbolic support provided during the process of individuation they enrich the psychic organization in adolescence, allowing behaviors and banishing others